Foliar Epidermal and Petiole Anatomical Studies of Some Nigerian Species of Ipomoea (Convolvulaceae) - Aworinde, David Olaniran; Ogundairo, Bushirat Odunayo; Erinoso, Sakiru Morenikeji; Sharaibi, Olubunmi Josephine (Current Botany, 2013)